Enhancing collaborative learning in online flexible distance learning higher education: The role of peer interaction and social presence mediated by learner self-efficacy - Mohamad, Liana; Osman, Zahir; Sugilar, S; Nurhayati, Suci (International Journal of Asian Social Science, 2025)
This study investigated the role of collaborative learning in flexible online distance education, focusing on the influence of peer interaction and social presence on learners' self-efficacy as a mediator. This study employed a questionnaire-based approach distributed to a sample selected through purposive sampling. Structural Equation Modeling (SEM) with SmartPLS4 software was used to analyze 388 data points. Results showed that all seven hypotheses were supported, with significant paths: peer interaction positively affects students' self-efficacy and collaborative learning, while social presence directly influences students' self-efficacy and collaborative learning. These findings suggest that increasing social presence and peer interaction can significantly improve students' collaborative learning outcomes by strengthening their self-efficacy. Future studies could examine the long-term effects, cultural differences, and integration of new technologies to provide a more immersive learning experience. This study also suggests developing a pedagogical framework based on the Community of Inquiry model to optimize collaborative online learning. The implications of this study are important for educators and institutions in enhancing online education by adopting strategies that can enhance social presence and peer interaction. Institutions can create more engaging and effective learning environments, increasing student confidence and fostering successful collaboration to improve academic achievement in the evolving digital education landscape.